PENINGKATAN KETERAMPILAN MENULIS KARANGAN NARASI MELALUI MEDIA GAMBAR SERI PADA SISWA KELAS III SEMESTER 2 SDN 1 WANASABA TAHUN PELAJARAN 2015/2016 - NFN Muharipin (MABASAN, 2017)
The study aimed at finding out the improvement of students’ writing skill in class III, Semester II SDN 1 Wanasaba, academic year 2015/2016. The subject of the study is Students of class III with a total of 23 students comprised of 10 males and 13 females. The study applies two cycles. Each cycle consists of four steps, namely are planning, application, observing/evaluating, and reflecting. The method used is observation, questioner/test, and documentation. Observation conducted to observe the execution process being conducted. Questioner/test is used to find out the result of learning and achievement. Documentation is for supplement material for teaching and learning process. The result of the study shows that the achievement of Students in class III, Semester II SDN 1 wanasaba, academic year 2015/2016 in learning bahasa Indonesia on writing a simple essay based on the serial pictures using correct words and sentences choice considering spelling, capital letters, and punctuation  before the application phase is very low. It is showed by the achievement of 26%. After the application of using serial pictures, the student’ achievement are better. It is showed in cycle 1, the result increases to 70% with good category. In cycle 2, the result increases to 100% with very good category.